Temperature-dependent rigidity and magnetism of polyamide 6 nanocomposites based on nanocrystalline Fe-Ni alloy of various geometries - M. A. A. Mohamed; D. Pedrazzoli; N. Nady; K. Kalaitzidou (eXPRESS Polymer Letters)
The focus of this study is to explore the potential use of Polyamide 6 nanocomposite reinforced with nanocrystalline (nc) Fe20Ni80 alloy (Fe20Ni80/PA6 PNC) in electromagnetic applications and provide understanding of how the alloy particle geometry is controlling the nanocomposite’s physical properties. Thermomechanical rigidity, room-temperature soft magnetic performance and thermal soft magnetic stability of Fe20Ni80/PA6 PNCs based on spherical-sea urchin alloy particles (UMB2-SU) and necklace-like alloy chains (UMB2-NC) have been investigated. Both PNCs have considerably superior bulk properties compared to neat PA6 and UMB2-SU exhibits the most remarkable overall performance. Morphological observations disclose two relevant phenomena: i) improved dispersion and distribution of the SU alloy particles than the NC ones within PA6 matrix, leading to stronger filler-matrix interfacial interactions within the UMB2-SU as compared to the UMB2-NC and ii) presence of constraint polymer regions in between alloy segments within the UMB2-SU that provide secondary reinforcing and soft magnetic mechanisms. Such phenomena along with the lower alloy crystallite size and PA6 γ-crystal type content within the UMB2-SU than in the UMB2-NC, are considered the main responsible factors for the distinctive performance of UMB2-SU. Overall, compared to various ferromagnetic nanocrystalline metallic materials, the research proposes the SU nc Fe20Ni80 alloy as a valuable nanofiller in polymers for electromagnetic applications.